Survey-Based Competitiveness Assessment of Restaurants and Cafés in Uzbekistan - Sobirov, Bobur (Academia Open, 2025)
General Background: Restaurants and cafés constitute an important component of the tourism value chain, contributing significantly to visitor expenditure and destination satisfaction. Specific Background: Despite the growth of food-service activities in Uzbekistan, systematic methods for measuring competitiveness at the establishment level remain limited. Knowledge Gap: Existing assessments provide insufficient integration of financial, service, digital, and human-resource dimensions into a single competitiveness measure for restaurants and cafés. Aims: This study develops and applies a structured survey instrument combined with a benchmark-normalization and weighted integral-index method to assess the competitiveness of restaurants and cafés serving tourism demand in Uzbekistan. Results: Using an illustrative sample of eight establishments across four Uzbek cities, the findings indicate that digital-ordering capability and customer satisfaction distinguish competitiveness more strongly than profitability alone. The results further show that casual-format cafés can achieve higher competitiveness scores than fine-dining restaurants when digital and customer-oriented indicators are strong. Novelty: The study introduces a survey-based competitiveness assessment framework that integrates profitability ratio, customer satisfaction, digital-ordering capability, and human-capital share into a single integral index while incorporating a sustainability-practice module for future development. Implications: The proposed framework provides a transparent benchmarking approach for food-service operators and industry associations and highlights the importance of format-stratified comparisons, broader competitiveness dimensions, and future incorporation of standardized sustainability indicators in restaurant and café evaluation. Highlights: • Digital-ordering capability and customer satisfaction distinguish competitive performance more strongly than profitability metrics. • Casual-format establishments achieve leading rankings when customer-oriented and technology-related indicators are strong. • The survey-based benchmarking framework combines financial, service, workforce, and digital dimensions into a unified assessment approach. Keywords: Restaurant Competitiveness, Café Performance, Integral Competitiveness Index, Digital Ordering Capability, Tourism Food Service